A desconstrução da ordem do discurso e a violência simbólica nas Orientações Curriculares Nacionais: em questão a identidade do sujeito-professor - Araújo, Alex Pereira de (2012)
About the national linguistic policy conveyed in the Portuguese National Curricular Guidelines in secondary education, whose discourse translates into a sophisticated method of control and an effective way of managing change, is what we seek to reflect in this work. In this sense, we can say that "every education system is a political way of maintaining or modifying the appropriation of discourses, with the knowledge and powers they bring with them" (FOUCAULT, 1996, p. 45). Based on the discursive-deconstructive approach (CORACINI, 2003a), we intend to present and discuss the analyzed results, whose focus is on the representations of identity(ies) and competencies constructed for teachers in this discourse, social representations of the teaching profession professor in contemporary Brazilian society, marked by the events that followed the dictatorial period, therefore, the phase of redemocratization of the country and modernization of the State in the face of the demands of globalization.